Acting for film: truth 24 times a second. - Churcher, Mel. (London, UK : Virgin Books, 2007)
What makes film acting different from acting on stage or TV? This book is a guide designed for actors already working in film, for those who want to, as well as for directors, teachers and anyone interested in film acting.
Acquisitions record.
Format: Paperback.
P.B
P.B
General.
Keywords: Motion picture acting